Effect of ear canal pressure and age on wideband absorbance in young infants. - Aithal, Sreedevi; Aithal, Venkatesh; Kei, Joseph (International Journal of Audiology, 2017)
Objective: The study investigated the effect of ear canal pressure and age on wideband absorbance (WBA) in healthy young infants. Design: Using a cross-sectional design, WBA at 0.25 to 8 kHz was obtained from infants as the ear canal pressure was swept from +200 to −300 daPa.Study sample: The participants included 29 newborns, 9 infants each at 1 and 4 months and 11 infants at 6 months of age who passed distortion product otoacoustic emissions test.Results: In general, negative-ear canal pressures reduced WBA across the frequency range, while positive-ear canal pressures resulted in reduced WBA from 0.25 to 2 kHz and above 4 kHz with an increase in absorbance between 2 and 3 kHz compared to WBA at ambient pressure. The variation in WBA below 0.5 kHz, as the pressure was varied, was the greatest in newborns. But, the variation was progressively reduced in older infants up to the age of 6 months, suggesting stiffening of the ear canal with age.Conclusions: Significant changes in WBA were observed as a function of pressure and age. In particular, developmental effects on WBA were evident during the first six months of life.